2017
DOI: 10.1002/jeab.255
|View full text |Cite
|
Sign up to set email alerts
|

Noncontingent reinforcement competes with response performance

Abstract: Noncontingent reinforcement is a commonly used procedure to decrease levels of problem behavior. Goals of this intervention are to decrease motivation, responding, and the functional relation between behavior and consequences, but it could also possibly compete with performance of alternative desirable responses. In the current study, we assessed the effects of noncontingent reinforcement arranged from 0% to 100% of sessions on performance of alternative responding across two experiments. Experiment 1 assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…Data similar to those of the present study can be found in Kelley, Nadler, Rey, Cowie, and Podlesnik (2017). The authors conducted a translational study to verify the effects of noncontingent reinforcement at different densities on problem behavior and the acquisition of desirable alternative responses.…”
Section: Discussionsupporting
confidence: 81%
“…Data similar to those of the present study can be found in Kelley, Nadler, Rey, Cowie, and Podlesnik (2017). The authors conducted a translational study to verify the effects of noncontingent reinforcement at different densities on problem behavior and the acquisition of desirable alternative responses.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the momentary variables influencing instances of resurgence remain to be determined. Assessments employing both animals and human participants are well suited to demonstrating the generality of effects (see also Kelley, Liddon, Ribeiro, Greif, & Podlesnik, ; Kelley, Nadler, Rey, Cowie, & Podlesnik, ; Nevin et al, ) while providing a platform from which to devise methods to mitigate resurgence of problem behavior resulting from omissions of alternative reinforcement during DRA treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The past decade witnessed a tendency for coupled/comparative studies, in which the results obtained from avian and human subjects were jointly analyzed. Most of these studies tackled different behavioral features of diagnostic or therapeutic significance of ASD ( Koshiba et al, 2016 ; Kelley et al, 2017 ; Galizio et al, 2020 ; Shvarts et al, 2020 ). In addition, molecular neuroanatomical studies, carried out on multiple species, including man, have also been reported, e.g., for the comparative localization of FMRP (see above) in the auditory system ( Wang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%